A Developmental Model of Interreligious Competence - Morgan, Jonathan (Archive for the psychology of religion, 2016)
This paper articulates a developmental model for how individuals relate to religious difference. We begin by reviewing scholarly work on multicultural competencies and initial research on religious diversity. To provide a framework for our model, we explore the Developmental Model of Intercultural Sensitivity and its relationship to research within the psychology of religion. The review closes by examining and critiquing a preliminary model of interreligious sensitivity. From this multi-faceted review, we propose a developmental model of interreligious competence and suggest key psychological capacities that undergird the model. Two case studies ground the theory before we explore future directions for research. Throughout, we consider the philosophical issues of alterity that shape encounters with religious diversity. By developing this model of interreligious competence, this article aims to provide a framework to help psychologists and other human service professionals become more effective in their interactions across religious difference.